Autonomy’s Ghost and General Education - Sadler, Simon 1968- (2013)
Arriving in the US a decade ago as a UK-trained architectural historian, I became more aware than I had been at home of what seemed like a disciplinary split between architectural historians trained as architects—thinking, perhaps, as architects—and architectural historians, thinking first and foremost as historians, for whom architecture was not an avocation. Jorge Otero-Pailos’s explanation of this cultural divide, which he describes in his Architecture’s Historical Turn: Phenomenology and the Rise of the Postmodern from 2010, was revelatory to me. The phenomenological turn in architecture led to nothing less than a redirection of architectural history as a profession, in which architects practicing as historians—’architect-historians’, as Otero-Pailos calls them—were found ‘staking out a new position … within the academy as the custodians of architecture’s peculiarly ambiguous mode of intellectuality’, which is the ‘unity of theory and practice’ (Otero-Pailos 2010: xiii). Two modes of architectural historical study now co-existed, particularly, it would seem, in the US, uneasily demarcating architect-historians, trained principally as architects, from architectural historians principally steeped in art historical methodology.
Keywords: Postmodernism, political economy, autonomy, general education